Bioavailability Studies of Metals in Surface Water of River Challawa, Nigeria. (15th September 2014) - Uzairu, A.; Okunola, O. J.; Wakawa, R. J.; Adewusi, S. G.
Abstract : Due to industrialization of Kano City, more industries located within Challawa industrial estate have discharged waste informed of effluents into River Challawa, which is the main source of irrigation water for agricultural land. Hence, this study is aim at assessing the bioavailable fractions of the metals zinc (Zn), lead (Pb), copper (Cu), chromium (Cr) and cadmium (Cd) in surface water of river Challawa, Kano, Nigeria, across seasons. It was found that the concentrations of most metals increased significantly during the dry seasons. Concentrations of Cu and Zn are within the standard limits of EPA and WHO for these metals in drinking water while Pb, Cr, and Cd have their concentrations higher than EPA and WHO standard limits. Analysis of relationship between metals indicated significant positive correlation (P < 0.05 ) between Cr and Zn, in all seasons with exception of warm and dry season. This might explain the consistent variation of these metals in the sites in a particular season. Also, significant negative correlation was observed between Cd and Cu (hot and dry season). The chemical fractionation trends were found to be dominated by particulate fractions of metals studied except Zn (cool and dry season) and Cd. The highest percentages of all metals analysed were found in the particulate fraction with exception of Cd. This could reflect less availability of this metal to the immediate environment. However, availability of metals such as Cd, Cr, and Pb in the dissolved and mobile fractions reflects the greater tendency to become available to the aquatic system and through the food chain to man.